2010
DOI: 10.1161/circulationaha.109.902148
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Recording of Cardiac Arrhythmias With an Implantable Cardiac Monitor in Patients With Reduced Ejection Fraction After Acute Myocardial Infarction

Abstract: for the Cardiac Arrhythmias and Risk Stratification After Acute Myocardial Infarction (CARISMA) Study Group Background-Knowledge about the incidence of cardiac arrhythmias after acute myocardial infarction has been limited by the lack of traditional ECG recording systems to document and confirm asymptomatic and symptomatic arrhythmias. The Cardiac Arrhythmias and Risk Stratification After Myocardial Infarction (CARISMA) trial was designed to study the incidence and prognostic significance of arrhythmias docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(94 citation statements)
references
References 34 publications
(21 reference statements)
8
83
1
2
Order By: Relevance
“…First-shock efficacy was 99% (n=79 of 80), and post-VT/VF survival was 90% (n=72 of 80). Consistent with other studies of sudden death events, 58 a substantial number of sudden cardiac arrests were attributable to non-VT/VF events (25%), including 23 asystole events.…”
Section: Clinical Experience With Wcdssupporting
confidence: 90%
“…First-shock efficacy was 99% (n=79 of 80), and post-VT/VF survival was 90% (n=72 of 80). Consistent with other studies of sudden death events, 58 a substantial number of sudden cardiac arrests were attributable to non-VT/VF events (25%), including 23 asystole events.…”
Section: Clinical Experience With Wcdssupporting
confidence: 90%
“…4 As many devices with different characteristics are available, the choice of the most suitable monitoring system largely depends on the likelihood of detecting a significant correlation between symptoms and ECG findings. 1 …”
Section: Cardiac Monitoring Systemsmentioning
confidence: 99%
“…2 Locati and colleagues reported a similar diagnostic yield over 1 month between ELRs and ILRs in presyncope, syncope and palpitations. 4 The authors concluded that an ELR may be indicated for the initial screening of patients with recurrent unexplained syncope or presyncope in place of a more expensive ILR, which remains an option if, after 1 month, monitoring with an ELR has proven negative. 13 The International Study on Syncope of Uncertain Etiology (ISSUE-1) study showed that the majority of syncopal events documented with an ILR is likely to be neurally mediated, with asystolic pauses and reflex bradycardia being the most frequently associated rhythm disturbances.…”
Section: Loop Recorders In Syncope and Palpitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RAFT trial suggested that, compared to ICD, CRT-D did not reduce morbidity or mortality in patients with atrial fibrillation [16]. Bradyarrhythmias may be an important cause of sudden death in patients with heart failure [67], and this may be one of the reasons why CRT, even without a defibrillator function, can reduce the risk of sudden death [68,69]. Whether CRT-D is superior to CRT alone is uncertain.…”
mentioning
confidence: 99%